The Utility of Cardiac Reserve for the Early Detection of Cancer Treatment-Related Cardiac Dysfunction: A Comprehensive Overview - Foulkes, Stephen; Claessen, Guido; Howden, Erin J.; Daly, Robin M.; Fraser, Steve F.; La Gerche, Andre (Frontiers in Cardiovascular Medicine, 2020)
With progressive advancements in cancer detection and treatment, cancer-specific survival has improved dramatically over the past decades. Consequently, long-term health outcomes are increasingly defined by comorbidities such as cardiovascular disease. Importantly, a number of well-established and emerging cancer treatments have been associated with varying degrees of cardiovascular injury that may not emerge until years following the completion of cancer treatment. Of particular concern is the development of cancer treatment related cardiac dysfunction (CTRCD) which is associated with an increased risk of heart failure and high risk of morbidity and mortality. Early detection of CTRCD appears critical for preventing long-term cardiovascular morbidity in cancer survivors. However, current clinical standards for the identification of CTRCD rely on assessments of cardiac function in the resting state. This provides incomplete information about the heart’s reserve capacity and may reduce the sensitivity for detecting sub-clinical myocardial injury. Advances in non-invasive imaging techniques have enabled cardiac function to be quantified during exercise thereby providing a novel means of identifying early cardiac dysfunction that has proved useful in several cardiovascular pathologies. The purpose of this narrative review is (1) to discuss the different non-invasive imaging techniques that can be used for quantifying different aspects of cardiac reserve; (2) discuss the findings from studies of cancer patients that have measured cardiac reserve as a marker of CTRCD; and (3) highlight the future directions important knowledge gaps that need to be addressed for cardiac reserve to be effectively integrated into routine monitoring for cancer patients exposed to cardiotoxic therapies.